Early responses to adenoviral-mediated transfer of the aquaporin-1 cDNA for radiation-induced salivary hypofunction - Baum, Bruce J; Alevizos, Ilias; Zheng, Changyu; Cotrim, Ana P; Liu, Shuying; McCullagh, Linda; Goldsmith, Corinne M; Burbelo, Peter D; Citrin, Deborah E; Mitchell, James B; Nottingham, Liesl K; Rudy, Susan F; et al. (Proceedings of the National Academy of Sciences - PNAS, 2012)
No conventional therapy exists for salivary hypofunction in surviving head and neck cancer patients with Radiation Therapy Oncology Group late grade 2–3 toxicity. We conducted a phase I clinical trial to test the safety and biologic efficacy of serotype 5, adenoviral-mediated aquaporin-1 cDNA transfer to a single previously irradiated parotid gland in 11 subjects using an open label, single-dose, dose-escalation design (AdhAQP1 vector; four dose tiers from 4.8 × 10 ⁷ to 5.8 × 10 ⁹ vector particles per gland). Treated subjects were followed at scheduled intervals. Multiple safety parameters were measured and biologic efficacy was evaluated with measurements of parotid salivary flow rate. Symptoms were assessed with a visual analog scale. All subjects tolerated vector delivery and study procedures well over the 42-d study period reported. No deaths, serious adverse events, or dose-limiting toxicities occurred. Generally, few adverse events occurred, and all were considered mild or moderate. No consistent changes were found in any clinical chemistry and hematology parameters measured. Objective responses were seen in six subjects, all at doses <5.8 × 10 ⁹ vector particles per gland. Five of these six subjects also experienced subjective improvement in xerostomia. AdhAQP1 vector delivery to a single parotid gland was safe and transfer of the hAQP1 cDNA increased parotid flow and relieved symptoms in a subset of subjects.